Ideas Plus A Collection of Practical Teaching Ideas. Book Eight. - National Council of Teachers of English, Urbana, IL.; National Council of Teachers of English, Urbana, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Contributed by English teachers across the United States, the activities contained in this booklet are intended to promote the effective teaching of English and the language arts. Teaching strategies offered in the first section of the booklet are designed to stimulate language exploration and include activities where students improvise dialogue and action between two characters, write and arrange readings for three voices, distinguish between fact and inference, work on discussion skills in a structured group discussion, connect concrete images with abstract concepts, and transform original fables into filmstrips. Activities in the second section are designed to stimulate an appreciation and understanding of literature and include focusing on imagist poetry, writing ghost chapters, group role playing, creating the "last words" of famous literary characters, staging a contemporary storytelling contest, and more. Teaching ideas in the third section provide the means for students to learn writing from a variety of different angles and for different purposes. Through this process students become confident, effective writers. Activities include outlining a draft, using Rube Goldberg cartoons as a basis for talking and writing about cause and effect, and practicing descriptive writing by "magnifying the moment." (SR)
Availability: National Council of Teachers of English, 1111 Kenyon Road, Urbana, IL 61801.
ERIC Note: For Book Seven, see ED 308 544.
Educational level discussed: Elementary Secondary Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Class Activities; Creative Writing; Educational Games; Elementary Secondary Education; English Instruction; Language Arts; Language Usage; Learning Activities; Literature Appreciation; Speech Skills; Student Motivation; Teaching Methods; Writing Exercises; Writing Improvement; Writing Instruction; Writing Processes; Guides, Classroom -- Teacher